(untitled) (Journal of Biodiversity Conservation and Bioresource Management, 2021)
Effects of various organic manures on the growth, performance and biomass production of Mahogany seedlings, an experiment was carried out in the net house of the Department of Soil, Water and Environment, University of Dhaka. Nine types of manures, viz. Kazi, ACI, Payel, BGF-1, Mazim, SK, Supermill, Sebok, Sufola organic manures were used separately at the rate of 12 ton/ha. Another dose of NPK inorganic fertilizer was used at the rate of 5kg/ha N, 3 kg/ha P, 3 kg/ha K respectively. Height, leaf area, and fresh and dry weights of leaf varied significantly (p≤ 0.5) and increased with time. Maximum leaf number (41.33 no./plant) and branch (6.33 no./plant) was found in Payel compost but maximum N concentration (2%) in leaf was obtained in Sebok treatment. Highest plant height (48.33 cm), leaf area (204.766 cm2/plant), girth (3.067 cm/plant), fresh weight (37.79g/plant), dry weight (9.16 g/plant), and length of petiole (6.33 cm) were recorded in Supermill treatment at harvest. Results showed that the overall best growth performance of seedlings was achieved in Supermill compost. J. Biodivers. Conserv. Bioresour. Manag. 2020, 6(2): 19-26